ASTRONOMICAL CALIBRATION OF THE UPPER LANGHIAN/LOWERSERRAVALLIAN RECORD OF RAS IL PELLEGRIN SECTION (MALTA ISLAND, CENTRAL MEDITERRANEAN) (Rivista italiana di Paleontologia e Stratigrafia, 2002)
A high-resolution geochemical and micropaleontological data set has been obtained from the uppermost Langhian/lower Serravallian marly sediments of the Ras il Pellegrin section (Malta Island). A combination of the recorded stratal organization with the results of spectral analyses performed on CaCO3 data and faunal signals shows a dominance of the classic Milankovitch periodicities as modulating forcing of the studied succession. The application of band-pass filters allowed us to select the different Milankovitch frequencies (precession, obliquity and short- and long-eccentricity) from the original faunal and geochemical signals and to compare them with the same components of the astronomical curve. The reliability of the short-term astronomical tuning has been tested by using the larger-order cyclicity (100-400 kyr) as control. The good match of the different records with the selected insolation curve is consistent with the results of the cross-spectral analysis showing high coherency values in all the considered frequency bands. The calibration provided astronomical ages for the sedimentary cycles and consequently for all the bioevents recorded in the section. In particular, an age of 13.59 Ma has been obtained for the last occurrence (LO) of Sphenolitus heteromorphus, at present considered the best bioevent useful for recognizing the Langhian/Serravallian boundary. Moreover, an age of 12.62 Ma has been obtained for the first occurrence (FO) of Paragloborotalia partimlabiata.